Keadilan Distributif dalam Ekonomi Islam: Analisis Filosofis dan Implikasinya terhadap Ketimpangan Sosial-Ekonomi - Kasmawati, Kasmawati; Mawardi, Mawardi (Program Pascasarjana IAIN Langsa, 2025)
The concept of distributive justice in Islamic economics presents an alternative to capitalist economic systems that often lead to inequality and social disparity. While capitalism prioritizes profit and market freedom, Islamic economics emphasizes equitable wealth distribution grounded in the values of tauhid (oneness of God), khilafah (stewardship), and maslahah (public interest). This study aims to critically analyze how the principles of distributive justice in Islamic economics can address contemporary issues of economic inequality and social injustice. Employing a descriptive qualitative method through an integrative literature review, this research examines classical Islamic economic texts and contemporary scholarly works, focusing on themes of justice, wealth redistribution, and ethical governance. The findings indicate that Islamic economic justice requires not only the prohibition of exploitative practices such as riba and monopoly but also active state involvement in regulating distribution and promoting social welfare. The integration of moral values such as justice, amanah (trust), and social responsibility into policy-making is essential for achieving sustainable and inclusive economic development. The study concludes that the framework of Islamic distributive justice offers a holistic and value-driven approach to economic policymaking, with potential applications in addressing structural poverty and fostering a just society.